Strategic research on the digital transformation of agricultural businesses based on evolutionary game theory - Rong, Mei; Hu, Huiyang; Qu, Zhaozhuo (Frontiers in Sustainable Food Systems, 2025)
The rapid progress of the digital economy has established digital transformation as a fundamental strategy for enterprises seeking to ensure sustainability, enhance competitiveness, and achieve sustained growth. Compared to other industries, the agricultural sector lags significantly in adopting digital transformation, requiring substantial efforts to bridge the existing gap. This paper constructs an evolutionary game model to analyze the strategic interactions and system evolution among agricultural businesses, digital enablers, and the government. It examines how strategic decisions, initial willingness, and parameter variations affect the dynamics of the system. Furthermore, the study utilizes Matlab2023b to simulate and analyze the evolutionary behaviors of the three parties, offering insights into their decision-making processes and mutual adaptations. The results of the study show that: (1) The internal drive of agricultural businesses is the primary factor influencing their active digital transformation strategy, while digital enablers assist in this process, primarily motivated by their own interests. Meanwhile, the government assumes a critical role in guiding and promoting the digital transformation of agricultural businesses; (2) Enhancing the initial willingness of stakeholders in the game, combined with fostering the synergistic benefits of collaborative transformation between agricultural businesses and digital enablers, significantly strengthens their motivation to actively engage in the transformation process. However, this dynamic tends to slow down the evolution of the government‘s adoption of an active regulatory strategy; (3) Government subsidies, paired with a structured system of rewards and penalties for agricultural businesses and digital enablers, effectively foster active engagement in the transformation process. Nevertheless, excessively generous subsidies and rewards risk undermining the government's ability to effectively execute its primary responsibility of proactive regulation. The findings elucidate the intrinsic logical interconnections between government regulation, digital enablers support, and agricultural enterprise transformation during the digitization process. Additionally, they illuminate the factors shaping the strategic decisions of these three parties, with the overarching goal of advancing the digital transformation of agricultural businesses.